2018
DOI: 10.3390/v10090489
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle Disease Virus V Protein Promotes Viral Replication in HeLa Cells through the Activation of MEK/ERK Signaling

Abstract: Newcastle disease virus (NDV) can infect a wide range of domestic and wild bird species. The non-structural V protein of NDV plays an important role in antagonizing innate host defenses to facilitate viral replication. However, there is a lack of knowledge related to the mechanisms through which the V protein regulates viral replication. The extracellular signal-regulated kinase (ERK) signaling pathway in the host is involved in a variety of functions and is activated by several stimuli, including viral replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Activation of the MEK/ERK signaling pathway has been observed as a positive factor in promoting viral replication in cells during various viral infections (Albarnaz et al, 2014; Shi et al, 2014; Takahashi and Suzuki, 2015). In previous findings, the MEK/ERK signaling pathway activity could facilitate NDV replication, and V protein played a vital role in activating the pathway (Chu et al, 2018). We therefore doubted whether MEK/ERK was involved in the induction of SOCS3 during NDV infection.…”
Section: Discussionmentioning
confidence: 88%
“…Activation of the MEK/ERK signaling pathway has been observed as a positive factor in promoting viral replication in cells during various viral infections (Albarnaz et al, 2014; Shi et al, 2014; Takahashi and Suzuki, 2015). In previous findings, the MEK/ERK signaling pathway activity could facilitate NDV replication, and V protein played a vital role in activating the pathway (Chu et al, 2018). We therefore doubted whether MEK/ERK was involved in the induction of SOCS3 during NDV infection.…”
Section: Discussionmentioning
confidence: 88%
“…The MEK/ERK signaling pathway regulates cancer cell proliferation, apoptosis, inflammation, angiogenesis, metastasis and drug resistance. In our previous work, we found that the V protein promotes viral replication in HeLa cells through the activation of the MEK/ERK signaling pathways [ 10 ]. Moreover, NDV selectively infects dividing cells and promotes viral proliferation [ 19 ], and these previous studies suggest that viral proteins may regulate viral replication by affecting cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In general, apoptosis of host cells can inhibit viral replication, and the V protein is known for its antiapoptotic activity [ 7 9 ]. In our previous study, we showed that the V protein can activate MEK/ERK signaling in HeLa cells [ 10 ]. Another study showed that the V protein can upregulate cytokine signaling 3 expression, and cytokine signaling 3 overexpression in chicken embryo fibroblast cells can activate the MEK/ERK signaling pathway [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The V protein, as a non-structural protein, is thought to be an interferon antagonist and is also associated with the virulence of NDV viruses [9]. Recent studies have shown that the V protein can mediate the promotion of NDV replication by participating in the ERK signalling pathway [10], while M is related to virus assembly and germination [11,12].…”
Section: Ivyspring International Publishermentioning
confidence: 99%